The impact of heterogeneous signals on stock price predictability in a strategic trade model - Christoph Winter (University of Basel, Center of Business and Economics (WWZ), 2018)
Generalizing the idea that price momentum can be explained by different levels of uncertainty inherent in the information structure, we implement signal-specific differences in uncertainty in a Kyle type model of strategic trading. We derive the equilibrium in a single-auction setting as well as a two-trading-period model. We show that the two-period equilibrium supports price patterns like momentum and reversal/under- and over-reaction without relying on any additional behavioral assumptions. Furthermore, the two-period setting can be extended to a multiple-trading-period equilibrium model with very similar equilibrium conditions to the original sequential auction equilibrium proposed by Kyle (1985), while preserving the price pattern of the two-period model.
Keywords: D43; D82; G12; G14; 330; Market structure; Asset Pricing; Market Efficiency; Asymmetric Information; Equilibrium